2022
DOI: 10.25259/ijdvl_1054_2021
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of IL36RN and CARD14 mutations with clinical manifestations and laboratory findings in patients with generalised pustular psoriasis

Abstract: Background Generalized pustular psoriasis (GPP) is a chronic disease associated with genetic factors related to mutations of the interleukin 36 receptor antagonist gene (IL36RN) and the caspase recruitment domain 14 gene (CARD14). However, the relevance of these mutations to the clinical features and severity of GPP remains unclear. Aims Our objective was to correlate the presence of IL36RN and CARD14 mutations with the clinical and laboratory findings in patients with GPP. Methods This cross-sectional des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
2
9
4
Order By: Relevance
“…Unlike other studies 10,16,17 which showed that IL36RN mutations predict a higher risk of systemic inflammation, defined as fever >38°C and leucocytosis >12 × 10 8 /L, we found no difference in the rate of fever, leucocytosis in the two patient groups. As previously described in the literature, 10‐12,16,17 we also found that the age of disease onset was significantly lower in patients with than those without IL36RN mutations (mean age:30.6 vs. 39.2 years, p = 0.027). However, we are not able to confirm the reported dosage effect of IL36RN on disease onset.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Unlike other studies 10,16,17 which showed that IL36RN mutations predict a higher risk of systemic inflammation, defined as fever >38°C and leucocytosis >12 × 10 8 /L, we found no difference in the rate of fever, leucocytosis in the two patient groups. As previously described in the literature, 10‐12,16,17 we also found that the age of disease onset was significantly lower in patients with than those without IL36RN mutations (mean age:30.6 vs. 39.2 years, p = 0.027). However, we are not able to confirm the reported dosage effect of IL36RN on disease onset.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent studies from Vietnam and China also showed a significantly higher prevalence of geographic tongue (GT) in patients who carried the c.115 + 6 T > C allele. 17,26 Unlike other studies 10,16,17 which showed that IL36RN mutations predict a higher risk of systemic inflammation, defined as fever >38°C and leucocytosis >12 × 10 8 /L, we found no difference in the rate of fever, leucocytosis in the two patient groups. As previously described in the literature, [10][11][12]16,17 we also found that the age of disease onset was significantly lower in patients with than those without IL36RN mutations (mean age:30.6 vs. 39.2 years, p = 0.027).…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations